Catalytic Hydrogen Isotope Exchange Reactions in Late-Stage Functionalization - Kang, Qi-Kai; Shi, Hang (Synlett, 2021)
The introduction of deuterium and tritium into molecules is of great importance in drug discovery. Many attempts have been made to develop late-stage hydrogen isotope exchange (HIE) reactions to avoid multistep syntheses using commercially available labeled precursors. In this review, we summarize recent progress in catalytic HIE reactions, with our main focus on their applications in the late-stage labeling of bioactive complex molecules and pharmaceuticals1 Introduction2 Non-Transition-Metal-Catalyzed Hydrogen Isotope Exchange2.1 Organocatalysis2.2 Photoredox Catalysis3 Transition-Metal-Catalyzed Hydrogen Isotope Exchang3.1 Palladium3.2 Ruthenium3.3 Iridium3.4 Other Metals4 Summary
Keywords: hydrogen isotope exchange reaction; late-stage functionalization; bioactive molecules; catalytic reaction; C–H functionalization; deuteration; tritiation